A signalling model of environmental overcompliance - Vincenzo Denicolò (Fondazione Eni Enrico Mattei (FEEM), 2000)
I model environmental overcompliance as a signalling device. In the model, a benevolent government may or may not tighten environmental standards. Production costs under the stricter environmental regulation are private information to the firms, and tightening environmental policy is socially desirable only if such costs are sufficiently low. The key assumption of the model is that firms differ in the cost of complying, and so those firms that enjoy a comparative advantage may actually benefit from tighter regulation. In these circumstances, such firms may overcomply in order to signal to the government that compliance costs are low, thus inducing the government to enforce stricter regulation.
Keywords: L13; K32; L50; Q20; 330; Environmental regulation; overcompliance; signalling; asymmetric firms; Umweltstandard; Umweltpolitik; Folgekosten; Asymmetrische Information; Signalling; Theorie